Occupations and the Non-Standard Employment Career: How the Occupational Skill Level and Task Types Influence the Career Outcomes of Non-Standard Employment. (June 2020) - Mattijssen, Lucille; Pavlopoulos, Dimitris; Smits, Wendy
This article examines to what extent the occupational skill level and task types determine whether non-standard employment (NSE) leads to a stepping-stone or a trap in the careers of workers. For this purpose, a typology of the individual careers of workers in the Netherlands who entered non-standard employment in 2007 is created using multichannel sequence analysis. This typology allows for classifying careers in terms of employment security and income security. An analysis of this typology shows that working in occupations with high-level tasks does not preclude trap careers with low levels of employment and income security. Routine tasks do not have an unequivocal effect on career outcomes, while manual tasks generally lead to trap careers. The combination of routine and manual tasks makes it most likely for NSE to function as a trap in workers' careers.